Pemanfaatan Media Sosial Pada Akun Instagram @mau.benerbareng Sebagai Media Dakwah Terhadap Perubahan Sikap Followers - Fasluki Subul; Muhammad N Abdurrazaq (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Carrying out the task of da'wah is an obligation for every Muslim. Da'wah has the main goal of changing human behavior from negative behavior to positive behavior. Achieving this da'wah goal requires da'wah media that can convey da'wah messages. One of the da'wah media used is social media. This study aims to determine the use of Instagram on the @mau.bendabareng account as a propaganda medium and to find out the changes in attitudes that occur in the followers of the @mau.bendabareng account. This study uses a qualitative research method with a qualitative descriptive approach. The results showed that the use of social media Instagram account @mau.benerbareng as a medium of da'wah through animated audio-visual media. Account @mau.bendabareng using Instagramto seek information in the field of da'wah. And the Da'wah content in the @mau.benerbareng account post is taken from online studies, lectures by Ustadz or Ustadzah, snippets of verses from the Qur'an, Hadith and from everyday experience. Andthe occurrence of a change in attitude to the followers of the @mau.bendabareng account in social media. This was known during interviews with several followers of the @mau.bendabareng account who admitted that there had been changes in themselves, especially when using social media. Informants often post da'wah content on their personal social media accountsKeywords :Utilization, Social Media, Instagram, Attitude, Followers